Does Micro Health Insurance Solve the Problem of Providing Accessible Healthcare to the Poor? Evidence from Niramoy Project, Bangladesh - Rahman, Md. Mizanur; Chowdhury, Sakufa (Global Disclosure of Economics and Business, 2014)
Billion of people in the world are out of reach from the modern health care facilities and medicine. Micro health insurance is one of the methods of providing accessible health care facilities to the poor. Micro health insurance in Bangladesh provides basic health care at an affordable rate for the poor and the ultra-poor. The traditional insurance program consists of front cash at each stage of service delivery, but micro health insurance scheme with its partner-agent model based distribution channel cover the adequate risk protection, inclusivity of access, affordability and program sustainability. The results of the analysis showed that micro health insurance program in Bangladesh has improved at the present time, but the increased access cannot reduce the essential health-related costs of marginal household.JEL Classification Code: G22; J65